BENEATH THE SURFACE: EXPLORING A CASE OF LEFT CIRCUMFLEX ARTERY DISSECTION - Menon Tushar, MD (Elsevier, 2024)
Therapeutic Area: Other: Non Atherosclerotic Acute Coronary Syndromes ( Spontaneous Coronary Artery Disease) Case Presentation: A 53-year-old woman with a history of hypertension was initially discharged after an NSTEMI and left heart cath showing spontaneous coronary artery dissection (SCAD) in the left circumflex artery. She returned to the ER three days later with chest pain. Despite initial plans for discharge with aggressive BP management using a nitro drip, her rising troponin levels necessitated overnight observation. Further cardiac cath revealed extensive SCAD (originating in the distal left main, extending into the circumflex, and terminating in the left PDA, as well as the obtuse marginal branch), worsening from the last angiogram done a week ago, likely due to uncontrolled hypertension. She was admitted to the ICU for 48 hours for heparin therapy and strict BP control, and was later discharged with instructions for close outpatient cardiology follow-up. Background: SCAD emerges as an increasingly acknowledged etiology behind non-atherosclerotic acute coronary syndromes. SCAD is implicated in 0.1% to 0.4% of all acute coronary syndrome (ACS) occurrences and is re-sponsible for about 25% of ACS instances in women under 50 and less commonly in men ( less than 15% of instances affect men). Risk factors include female sex, pregnancy, fibromuscular dysplasia, and associations with genetic connective tissue disorders such as Marfan and Ehlers-Danlos syndromes. It most commonly occurs in the LAD artery. In 46 to 61% of instances, the diagonal and septal branches are also in-volved; 15 to 45% of cases involve the circumflex, ramus, and marginal branches. Affecting several coronary branches is uncommon, but may occur in 9 to 23% of patients. Diagnosis predominantly relies on coronary angiography, which identifies the false lumen and intramural hematoma resulting from intimal disruption and vasa vasorum bleeding. Treatment is primarily medical for cases without progression, hemodynamic instability, or significant myocardial involvement, utilizing aspirin, plavix, ACE inhibitors, beta blockers, and heparin. Refractory cases may necessitate interventional strategies like stenting, angioplasty, coronary artery bypass grafting (CABG), or percutaneous transluminal coronary angioplasty). Reoccurrence from HTN occurs in 10 to 30% of patients. Conclusions: SCAD is becoming recognized as the cause of acute myocardial infarction, particularly in young female patients with low cardiovascular risks.